Allogeneic CD34+ selected hematopoietic stem cell boost following CAR T‐cell therapy in a patient with prolonged cytopenia and active infection. Issue 3 (24th December 2022) - Lipsitt, Amanda; Beattie, Lisa; Harstead, Elaine; Li, Ying; Goorha, Salil; Maron, Gabriela; Gottschalk, Stephen; Triplett, Brandon; Naik, Swati
Abstract: Hematological toxicity (hematotoxicity) leading to peripheral cytopenias is a common long‐term adverse effect following the use of CD19‐chimeric antigen receptor (CD19‐CAR) T‐cell therapies. However, management remains unclear for patients whose cytopenias persist beyond 1 month after CAR T‐cell infusion. We present the case of a 21‐year old who received CD19‐CAR T‐cell therapy for relapse following a haploidentical transplant. He developed hematotoxicity and consequently multiple life‐threatening infections. We administered a CD34 + hematopoietic stem cell boost (HSCB) from his transplant donor, which led to hematopoietic recovery and resolution of his infections without any effect on the activity of CD19‐CAR T cells. CD34 + HSCB can be a safe and effective option to treat hematotoxicity following CD19‐CAR T‐cell therapy.